Does the use of a novel self-adhesive flowable composite reduce nanoleakage? - Abo El Naga A; Yousef M; Ramadan R; Fayez Bahgat S; Alshawwa L (Dove Medical Press, 2015)
Abeer Abo El Naga,1 Mohammed Yousef,1 Rasha Ramadan,2,3 Sherif Fayez Bahgat,4,5 Lana Alshawwa6 1Operative Dentistry Department, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 2Operative Dentistry Department, Modern Science and Arts University, Cairo, Egypt; 3Operative Dentistry Department, Dentistry Program, Batterjee Medical College, Jeddah, Saudi Arabia; 4Fixed Prosthodontics Department, Modern Science and Arts University, Cairo, Egypt; 5Fixed Prosthodontics Department, Dentistry Program, Batterjee Medical College, Jeddah, Saudi Arabia; 6Medical Education Department, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia Objective: The aim of the study reported here was to evaluate the performance of a self-adhesive flowable composite and two self-etching adhesive systems, when subjected to cyclic loading, in preventing the nanoleakage of Class V restorations. Methods: Wedge-shape Class V cavities were prepared (4×2×2 mm [length × width × depth]) on the buccal surfaces of 90 sound human premolars. Cavities were divided randomly into three groups (n=30) according to the used adhesive (Xeno® V [self-etching adhesive system]) and BOND-1® SF (solvent-free self-etching adhesive system) in conjunction with Artiste® Nano Composite resin, and Fusio™ Liquid Dentin (self-adhesive flowable composite), consecutively. Each group was further divided into three subgroups (n=10): (A) control, (B) subjected to occlusal cyclic loading (90N for 5,000 cycles), and (C) subjected to occlusal cyclic loading (90N for 10,000 cycles). Teeth then were coated with nail polish up to 1 mm from the interface, immersed in 50% silver nitrate solution for 24 hours and tested for nanoleakage using the environmental scanning electron microscopy and energy dispersive analysis X-ray analysis. Data were statistically analyzed using two-way analysis of variance and Tukey's post hoc tests (P≤0.05). Results: The Fusio Liquid Dentin group showed statistically significant lower percentages of silver penetration (0.55 µ) compared with the BOND-1 SF (3.45 µ) and Xeno V (3.82 µ) groups, which were not statistically different from each other, as they both showed higher silver penetration. Conclusion: Under the test conditions, the self-adhesive flowable composite provided better sealing ability. Aging of the two tested adhesive systems, as a function of cyclic loading, increased nanoleakage. Keywords: Class V, flowable composite, nanoleakage, cyclic loading, self-adhesive